Three bufadienolides induce cell death in the human lung cancer cell line CL1‐5 mainly through autophagy. (1st January 2021) - Huang, Hui-Chi; Chang, Wen-Te; Lee, Meng-Shiou; Chen, Hsing-Yu; Chen, Yu-Hua; Lin, Chi-Chen; Lin, Ming-Kuem
Graphical abstract: Abstract: The effects of 3 bufadienolides, namely kalantuboside B, kalantuboside A, and bryotoxin C, isolated from Kalanchoe tubiflora (Harvey) were evaluated and characterized in CL1-5 highly metastatic human lung cancer cells. In contrast to their apoptosis-promoting activity in other cancer cells, these bufadienolides only slight or did not induce apoptosis in CL1-5 cancer cells. Instead, they activated an autophagy pathway, as indicated by increased autophagosome formation. Autophagy induced by these bufadienolides was demonstrated to be linked to the down-regulation of p-mTOR and the up-regulation of LC3-II, ATG5, ATG7, and Beclin-1. Our findings revealed an autophagy as the alternative mechanism of drug action by bufadienolides in CL1-5 lung cancer cells and provided evidence that bufadienolides are a potential therapeutic strategy for highly metastatic human lung cancer.